Pengaruh penambahan alpha tocopherol terhadap kualitas semen entog yang disimpan pada suhu dingin (Faculty of Animal Science, Universitas Brawijaya, 2013)
The study was conducted to evaluate the effect alpha-tocopherol addition on the quality of muscovy duck semen during the storage process at 4 0C. The materials of the study were 4 male Muscovy ducks aged between 1.5 – 2.0 years old. Semen was collected twice a week and its quality was evaluated immediately after the collection. The collected semen was kept in refrigerator for 60, 120 and 180 minutes using a medium containing alpha-tocopherol 0; 0.2; 0.4 and 0.6 ppm. Then quality of the stored semen was evaluated. The study found that semen quality decreased during the storage process. The study concluded that addition of alpha-tocopherol was able to increase superoxide dismutase (SOD) activity and decrease the malondialdehide (MDA). Keywords: Muscovy duck semen, cold storage, alpha-tocopherol, SOD, MDA